Fit for Purpose Assessment: A New Direction for IACUCs. (4th May 2022) - Kinter, Lewis B; Johnson, David K; Weichbrod, Robert H; Prentice, Ernest D; Simmonds, Richard C; Houghton, Paul W; Whitney Jr, Robert A; DeGeorge, Joseph; DeHaven, W Ron; Kramer, Klaas; DeTolla, Louis
Abstract: The organization and function of the institutional animal care and use committee (IACUC) is the key component of government regulation and oversight of necessary scientific research using live animals and of AAALAC - International accreditation of animal care and use programs in the United States. The regulations, roles, and responsibilities of IACUCs have evolved since their inception 35 years ago from a limited focus on animal welfare and specific animal procedures to embracing scientific quality, data reproducibility and translation, and animal welfare as inextricably interdependent and critical components of generation of new scientific knowledge and medical treatments. A current challenge for IACUCs is in evaluating whether benefits to be derived (eg, new knowledge or treatments) justify any unavoidable pain, stress, or injury associated with proposed research protocols, because the former are long-term and at best speculative outcomes, whereas the latter are immediate and tangible for the study animals. Scientific consensus is that research most likely to generate significant new knowledge and medical treatments is that conducted to high scientific, technical, and quality standards and reported with full transparency to facilitate reproducibility. As an alternative to current benefits evaluations included in risk benefit and harm benefit constructs, the authors propose that IACUCs assess the proposed research for scientific quality and alignment of study elements with the study purpose (e.g., Fit for Purpose [FfP]), including justifications for study design components, selection of primary endpoints and technologies, rationale for data and statistical analyses, and research communication plans. Fit for Purpose endpoints are objective, immediate, and impactful as are the potential risks for study animals, and at the same time they are the best predictors for achievement of longer-term benefits. We propose that IACUCs and any revision of The ILAR Guide consider FfP concepts in place of traditional benefits assessment to accelerate the generation of new knowledge and treatments benefiting medical and veterinary patients and the environment through better science and animal welfare rather than to continue to rely on speculative future outcomes.